FRI0554 Poverty Modifies The Effect of Race on Total Knee Arthroplasty Outcomes. (15th July 2016) - Goodman, S.M.; Parks, M.L.; Bogardus, M.H.; Zhang, M.; Nguyen, J.T.; Lee, Y.-Y.; Figgie, M.P.; Mandl, L.A.; Bass, A.R.
Abstract : Background: Race is an important predictor of total knee arthroplasty (TKA) outcomes in the United States; however analyses of race can be confounded by socioeconomic factors. Objectives: To analyze the interaction between race and community poverty as it effects patient reported outcomes after TKA. Methods: We identified all patients undergoing TKA enrolled in a hospital based registry between 2007 and 2011, living in three adjacent states. Using geocoding we linked individual-level registry data including WOMAC pain and function to U.S. census tracts (CT) data. We constructed a multivariate linear mixed effect model within multilevel frameworks to assess the interaction between race and CT poverty on 2-year WOMAC outcomes. Results: Of 4225 TKA patients, 194 (4.6%) were black. Baseline WOMAC scores were statistically but not clinically significantly worse for blacks than for whites (WOMAC Pain 49 vs. 55, p<0.0001; WOMAC Function 47 vs. 54, p<0.0001; 100=best). Fewer blacks had a college education or above (45% vs. 62%, p<0.0001), and blacks had higher BMI (33 vs. 30, p<0.001) and more comorbidities than whites (44% >1 comorbidity vs. 27%, p<0.0001). More blacks lived in high poverty neighborhoods (37% vs. 3.5%, p<0.0001). Controlling for multiple potential confounders, our model demonstrated that whites and blacks from census tracts with <10% poverty have similar 2-year WOMAC scores. With increasing community poverty, pain and function worsened; from census tracts with >50% poverty blacks had clinically meaningful worse pain and function compared to whites (Table 1 ). Conclusions: We have found a significant differential effect of poverty on 2-year outcomes after TKA when stratified by race. Overall WOMAC scores are minimally but not significantly worse for blacks than whites. However, while outcomes among whites do not vary much between high and low poverty census tracts, the effect of high poverty levels was disproportionally associated with worse TKA outcomes among black Americans. Since a higher proportion of blacks live in high poverty areas, this finding has important implications. Efforts to improve TKA outcomes among U.S. blacks will need to investigate both the impact of individual patient-level factors and community-level poverty. Disclosure of Interest: None declared